Path-coefficient and correlation analysis in Bambara groundnut (Vigna subterranea [L.] Verdc.) accessions over environments - Khan, Md Mahmudul Hasan; Rafii, Mohd Y.; Ramlee, Shairul Izan; Jusoh, Mashitah; Al Mamun, Md (Nature Research, 2022)
In a breeding program, studies of genotypic and phenotypic relationships among agricultural crop traits are useful to design, evaluate, and develop selection criteria for desirable traits. Using path coefficient analysis, the present study was executed to estimate the phenotypic, genotypic, and environmental correlation coefficients between yield and yield-related traits and to determine the direct and indirect effects of yield-related traits on yield per plant. A total of 30 genotypes of Vigna subterranea were studied under tropical conditions at two sites over two planting seasons (considered as four environments). The experiment at each site used a randomized complete block design with three replicates. Data were collected on vegetative and yield component attributes. Based on analysis of variance, pooled results showed that there were positive and highly significant differences (p ≤ 0.01) among the 30 genotypes for all attributes studied. Highly significant and positive strong correlation at phenotypic level was observed for dry seed weight (0.856), hundred seed weight (0.754), fresh pod weight (0.789), and total pod weight (0.626) with yield in kg per hectare, while moderate positive correlations were observed for harvest cut (0.360) and days to maturity (0.356). However, a perfect positive correlation was observed for the dry weight of pods with seed yield. In contrast, days to 50% flowering (− 0.350) showed a negative significant relationship with yield per hectare. The dried pod weight attribute (1.00) had a high positive direct effect on yield. Fresh pod weight had the greatest indirect effect on yield per hectare, followed by the number of total pods by dry pod weight. As a result, dry pod weight, hundred seed weight, number of total pods, and fresh pod weight could be used as selection criteria to improve the seed yield of Bambara groundnut (Vigna subterranea).